2008
DOI: 10.1038/bjp.2008.332
|View full text |Cite
|
Sign up to set email alerts
|

Effects of excitatory and inhibitory neurotransmission on motor patterns of human sigmoid colon in vitro

Abstract: Background and purpose: To characterize the in vitro motor patterns and the neurotransmitters released by enteric motor neurons (EMNs) in the human sigmoid colon. Experimental approach: Sigmoid circular strips were studied in organ baths. EMNs were stimulated by electrical field stimulation (EFS) and through nicotinic ACh receptors. Key results: Strips developed weak spontaneous rhythmic contractions (3.67 ± 0.49 g, 2.54 ± 0.15 min) unaffected by the neurotoxin tetrodotoxin (TTX; 1 mM). EFS induced strong cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
101
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(122 citation statements)
references
References 39 publications
(64 reference statements)
18
101
1
Order By: Relevance
“…Animal studies described that NO released from inhibitory myenteric neurons controlled both the amplitude and the latency timing of the off-response in the distal smooth muscle esophagus (5) and mediated nerve-induced hyperpolarization of circular esophageal and LES smooth muscle (4, 6). These in vitro animal studies also found that inhibition of NOS with L-NNA or by blocking the NO-intracellular pathway with the guanylate cyclase inhibitor 1H- [1,2,4]oxadiazolo- [4,3-a]quinoxalin-1-one attenuated or even abolished the off-response and shortened the latency period, inducing the appearance of a cholinergic on-contraction of greater amplitude than the previous on-and off-contractions (5,20). In our human study, in vitro on and off EB contractions are similar to these previous in vitro animal studies and to the two types of esophageal peristaltic contractions found during in vivo vagal stimulation in the opossum esophagus (20).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Animal studies described that NO released from inhibitory myenteric neurons controlled both the amplitude and the latency timing of the off-response in the distal smooth muscle esophagus (5) and mediated nerve-induced hyperpolarization of circular esophageal and LES smooth muscle (4, 6). These in vitro animal studies also found that inhibition of NOS with L-NNA or by blocking the NO-intracellular pathway with the guanylate cyclase inhibitor 1H- [1,2,4]oxadiazolo- [4,3-a]quinoxalin-1-one attenuated or even abolished the off-response and shortened the latency period, inducing the appearance of a cholinergic on-contraction of greater amplitude than the previous on-and off-contractions (5,20). In our human study, in vitro on and off EB contractions are similar to these previous in vitro animal studies and to the two types of esophageal peristaltic contractions found during in vivo vagal stimulation in the opossum esophagus (20).…”
Section: Discussionmentioning
confidence: 81%
“…We found decreasing effects of the intrinsic cholinergic innervation from the EB to both sides of human LES, supporting the concept that amplitude of esophageal contractions is determined by a balance of these intrinsic circuits. Finally, the P2Y 1 receptor antagonist MRS2179 did not affect latency, but reduced amplitude of off-contractions, suggesting a modulation of cholinergic neurons by excitatory P2Y 1 receptors (1).…”
Section: Discussionmentioning
confidence: 84%
“…This lack of effect of TTX demonstrated the non-neuronal origin of rhythmic phasic contractions 27 and an unbalanced effect of TTX on excitatory and inhibitory enteric motor neurons could increase colonic contractility for a short time. Actually, first-stage gastrointestinal symptoms after TTX intoxication include nausea, vomiting, diarrhea, and abdominal pain, rather than paralytic ileus.…”
Section: Discussionmentioning
confidence: 99%
“…Purinergic receptors are present in numerous cell types since purines play a role in many cell com- Suramin and PPADs are scarcely selective purinergic antagonists that do not allow differentiation between distinct P2 receptors. The development of specific antagonists such as, for instance MRS2179, which blocks P2Y1 receptors (34;35), allowed to identify pharmacologically that ATP, acts post-junctionally through P2Y1 receptors causing smooth muscle relaxation in several GI tract areas (12,24,25,36,37). Subsequently, two new antagonists (MRS2279 and MRS2500) with greater affinity for the P2Y1 receptor, (35,38,39) confirmed the crucial role of this receptor subtype in purinergic neurotransmission.…”
Section: P2y 1 Receptor Identified As Responsible For Bowel Relaxationmentioning
confidence: 99%
“…In contrast. In contrast ATP may have a key role in transient relaxation as is, for instance, the case with the descending phase of the peristaltic reflex (24,26), and would therefore predominate in areas with more relevant peristalsis, including the small intestine and colon (17,19,24,25,30,36,37).…”
Section: Functional No-atp Co-transmissionmentioning
confidence: 99%